PREVALENCE OF BODY FAT DISTRIBUTION AMONG GENRES RELATED TO AGE GROUP AND PRESSURE LEVEL (Fiep Bulletin - online, 2013)
The main objective of this study is to charaterize the prevalence of the which body fat distribution between genders and specifically relate their age and pressure level. The research was conducted through the collection of data from individuals of a bodybuilding gym in the city of Maringá / PR. The final sample obtained (n = 80) was divided into 2 groups: group 1 (40 subjects, 20 males and 20 females, with age between 15 and 28 years) and group 2 (40 subjects, 20 men and 20 women, with age between 29 and 40 years). To the achievement of assessments, were identified the anthropometric measurements, weight, height, body circumferences, skinfold thickness of each individual and the pressure level. The qualitative and quantitative variables are presented in graph form with values ??expressed in percentages. The study shows that 65% of women (n = 13) and 55% of men (n = 11) or 35% of women (n = 7) and 45% of men (n = 9) of this study, between 15 and 28 years of age have higher fat accumulation in the abdominal region and supra iliac, respectively. Approaching the age group 29-40 years, the percentage of fat mass increased from 65% to 80% in women (n = 16) and 55% to 75% in men (n = 15), in the abdominal region. In the region supra iliac the fat percentage has decreased in both men (from 45 to 25%) and in women (from 35 to 20%) according to age compared. The tendency of developing hypertension is larger in men than in women. This study had achieved its objectives by identifying that many individuals need to be monitored by a professional the area of health as preventive medicine.
Keywords: Body fat distribution; age group and pressure level.